Europe in crisis, the left, and the challenge of migration. Issue 3 (2nd September 2019) - Gluhovic, Milija
ABSTRACT: Taking as a point of departure recent writing by theorists such as Seyla Benhabib, Michel Feher, and Slavoj Žižek, who have argued that the ongoing refugee crisis presents a unique opportunity for Europe to redefine itself, the essay traces the ways in which the crisis and related issues are represented in Elfriede Jelinek's play Charges (The Supplicants, 2015) and Yael Ronen and the Exile Ensemble's performance Winterreise (2018). The racialized, unsovereign bodies of migrants are always in the 'wrong' places, these works suggest, defined by transgression. Situating this analysis in relation to current debates about states of exceptionalism and new forms of neo-liberal governmentality under the conditions of globalisation, I ask about the intervention of such performances in the increasingly repressive European migration regimes? What is the role of the Left in reclaiming the material, social, and legal conditions for the acceptance of refugees in Europe? Moreover, what can be done to redress this humanitarian crisis and establish unity, solidarity, and hospitality in Europe against a transnational front of the forces rejecting refugees?